Computational Science and Its Applications -- ICCSA 2013 13th International Conference, Ho Chi Minh City, Vietnam, July 24-27, 2013, Proceedings, Part II - Murgante, Beniamino; Misra, Sanjay; Carlini, Maurizio; Torre, Carmelo; Nguyen, Hong-Quang; Taniar, David; Apduhan, Bernady O.; Gervasi, Osvaldo (Theoretical Computer Science and General Issues, 2013)
The five-volume set LNCS 7971-7975 constitutes the refereed proceedings of the 13th International Conference on Computational Science and Its Applications, ICCSA 2013, held in Ho Chi Minh City, Vietnam, in June 2013. Apart from the general track, ICCSA 2013 also include 33 special sessions and workshops, in various areas of computational sciences, ranging from computational science technologies, to specific areas of computational sciences, such as computer graphics and virtual reality. There are 46 papers from the general track, and 202 in special sessions and workshops.